Type A Trichothecene Diacetoxyscirpenol-Induced Emesis Corresponds to Secretion of Peptide YY and Serotonin in Mink - Wu, Qinghua; Kuca, Kamil; Nepovimova, Eugenie; Wu, Wenda (Toxins, 2020)
The trichothecene mycotoxins contaminate cereal grains and have been related to alimentary toxicosis resulted in emetic response. This family of mycotoxins comprises type A to D groups of toxic sesquiterpene chemicals. Diacetoxyscirpenol (DAS), one of the most toxic type A trichothecenes, is considered to be a potential risk for human and animal health by the European Food Safety Authority. Other type A trichothecenes, T-2 toxin and HT-2 toxin, as well as type B trichothecene deoxynivalenol (DON), have been previously demonstrated to induce emetic response in the mink, and this response has been associated with the plasma elevation of neurotransmitters peptide YY (PYY) and serotonin (5-hydroxytryptamine, 5-HT). However, it is found that not all the type A and type B trichothecenes have the capacity to induce PYY and 5-HT. It is necessary to identify the roles of these two emetogenic mediators on DAS-induced emesis. The goal of this study was to determine the emetic effect of DAS and relate this effect to PYY and 5-HT, using a mink bioassay. Briefly, minks were fasted one day before experiment and given DAS by intraperitoneally and orally dosing on the experiment day. Then, emetic episodes were calculated and blood collection was employed for PYY and 5-HT test. DAS elicited robust emetic responses that corresponded to upraised PYY and 5-HT. Blocking the neuropeptide Y2 receptor (NPY2R) diminished emesis induction by PYY and DAS. The serotonin 3 receptor (5-HT3R) inhibitor granisetron totally restrained the induction of emesis by serotonin and DAS. In conclusion, our findings demonstrate that PYY and 5-HT have critical roles in DAS-induced emetic response.
Keywords: antiemetika; Up-Regulation; Female; norek; granisetron; ženské pohlaví; modely nemocí na zvířatech; serotonin; zvracení; antagonisté serotoninových receptorů 5-HT3; Trichothecenes; Granisetron; Vomiting; Secretory Pathway; receptory serotoninové 5-HT3; receptory gastrointestinálních hormonů; Animals; Receptors, Serotonin, 5-HT3; peptid YY; sekreční dráha; zvířata; Antiemetics; Mink; Peptide YY; trichotheceny; Serotonin; upregulace; Receptors, Gastrointestinal Hormone; Disease Models, Animal; Serotonin 5-HT3 Receptor Antagonists